[Frank Forrest collection of music programmes, Sydney, ca. 1925-1950]. - Forrest, Frank, 1902-1998.; Sydney Philharmonia Choir; Hurlstone Park Choral Society (1916)
Collection contains programmes of religious choral performances and of classical and light classical choral performances, including the Hurlstone Park Choral Society performances (precursor to the Sydney Philharmonia Choir), held in the Sydney area from 1925-1950 in which Frank Forrest particpated. Advertisements, news clippings, eisteddfod adjudication reports also included.
Photographs Pictures collection, National Library of Australia
Tenor, active in musical life of Sydney from 1920s-1950s and a member of several choirs and groups including the ABC Male Quartet and the Radio Revellers. He studied at the Conservatorium of Music under Roland Foster and won many prestigious awards. He was the Tenor Champion in the Eisteddfod conducted to celebrate the opening of the Sydney Harbour Bridge. His musical career included regular broadcasts on Radio 2BL, 2FC, 2GB. He was appointed tenor soloist at the Sydney Central Methodist Mission from April 1926 until September 1953.
This collection is featured in the Guide to Australian Performing Arts Programs and Ephemera (PROMPT) Collections in the National Library of Australia
Keywords: Singers -- New South Wales -- Sydney -- Archives; Forrest, Frank, -- 1902-1998 -- Archives; Music -- New South Wales -- Sydney -- Performance; Concert programs -- New South Wales -- Sydney -- Collections; Theater programs -- Australia; Performing arts -- Australia; Printed ephemera -- Australia; Australian